2009
DOI: 10.1007/s00787-009-0748-6
|View full text |Cite
|
Sign up to set email alerts
|

The crown of love: intimate relations and alcohol use in adolescence

Abstract: Background: Remarkably, little attention has been paid to the role of intimate partners and their drinking behavior in relation to adolescent alcohol use. In the current study, we examined associations between adolescent alcohol use and romantic partners’ drinking behavior. Methods: A total of 428 families, consisting of both parents and two adolescents (aged 13.4 and 15.2 at Time 1) participated in a prospective study with four annual waves. Correlations and multivariate regressions were used to examine (1) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
0
12
0
1
Order By: Relevance
“…A romantic partner is the fourth most likely person to offer drugs to an adolescent, but is second only to a family member in terms of being difficult to refuse; approximately half of the offers from romantic partners are accepted (Trost, Langan, & Kellar-Guenther, 1999). Although van der Zwalau et al (2009) found no evidence for romantic partner socialization on adolescents’ alcohol use, these findings may reflect methodological issues resulting from source bias about alcohol use or data collected after relationships (and socialization) were initiated.…”
Section: Romantic Partner Socializationmentioning
confidence: 60%
See 1 more Smart Citation
“…A romantic partner is the fourth most likely person to offer drugs to an adolescent, but is second only to a family member in terms of being difficult to refuse; approximately half of the offers from romantic partners are accepted (Trost, Langan, & Kellar-Guenther, 1999). Although van der Zwalau et al (2009) found no evidence for romantic partner socialization on adolescents’ alcohol use, these findings may reflect methodological issues resulting from source bias about alcohol use or data collected after relationships (and socialization) were initiated.…”
Section: Romantic Partner Socializationmentioning
confidence: 60%
“…However, we know little about these types of selection effects during adolescence. In one of the few related studies, Dutch adolescents reported significant concordance in their own and their partners’ alcohol use (van der Zwalau, et al, 2009). However, in this as well as many other studies, reports of partner behavior were provided by participants after the relationship had begun, making it difficult to estimate pure selection effects.…”
Section: Romantic Partner Selectionmentioning
confidence: 99%
“…Thus, the adolescents most susceptible to partner influences may be those who find a romantic partner with levels of drug use widely divergent from their own. This is in contrast to van der Zwaluw and colleagues (2009); however, the results of this study utilized data from both individuals rather than having participants report on their partners substance use.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, studies have tended to rely on second-hand reports of substance use behavior rather than couple-based report (i.e. information gathered from both partners;van der Zwaluw et al, 2009). Lastly, previous research has drawn on primarily cross-sectional samples or retrospective survey data, thus prohibiting examination of these relations across time.…”
Section: Current Studymentioning
confidence: 99%
“…Another explanation involves selection, i.e. people seek other people exhibiting their preferred behaviours (Engels, Knibbe, Drop, & De Haan, 1997;Van der Zwaluw et al, 2009).…”
Section: Conclusion and Discussionmentioning
confidence: 99%